A study on the association of quality services and customer satisfaction: a case study at Renaissance Kota Bharu / Rozaina Ibrahim - Ibrahim, Rozaina (2004)
This research paper is focusing on customer perception and satisfaction on service quality provided at Renaissance Kota Bharu. The objective of the study is to determine the important factors used by the customer in choosing the hotel and resort and to identify the level of customers' perception and satisfaction towards the service quality provided. Furthermore, researcher want to identify the areas, which the delivery of the services provided by the resort can be improved. In the literature review, researcher examined the definition of the perception, customer satisfaction, service quality and employees, which relate in this study and give a clear view of the overall research. Beside that, researcher explained the component of service quality which consist the service reliability, responsiveness, assurance, tangibles and empathy as a guidance to measure the customers perception and satisfaction towards the service quality provided at Renaissance Kota Bharu. For this study, researcher collected primary and secondary data. The target populations for this study are among local and foreign tourist that comes to Renaissance Kota Bharu. SPSS (Statistical Packages for Social Science) program was used to analyze the questionnaires based on descriptive analysis. From the findings, researcher has identified the important factors used by customers in choosing the hotel and resort. Researcher also have identified the areas of the delivery of services, which need to improve by the resort. Here, researcher has come out with the recommendations and suggestions to improve the services provided at Renaissance Kota Bharu